Social work with autistic people : essential knowledge, skills and the law for working with children and adults - Dunn, Yo (Jessica Kingsley Publishers, 2020)
"This book will help social workers and practitioners to find achievable solutions to support autistic people -- including those with complex needs -- to live fulfilling lives in their communities. Far too many autistic people are currently in inappropriate institutional placements, putting their basic human rights at risk and experiencing a poor a poor quality of life. Good quality support for autistic people is achievable, even in a social care system under pressure. This book will help practitioners to develop high quality community support to facilitate discharges and prevent admissions, by providing them with effective, practical strategies to communicate with and more effectively support autistic people right across the spectrum. Common assumptions and beliefs are challenged, including the idea that 'behaviours' are an inevitable part of autism, and practical approaches are offered to promote autonomy, respect for human rights and empathy with autistic perspectives as a basis for preventing distressed behaviour. This will enable practitioners to support and empower all autistic people to achieve a good quality of life in their community."--Publisher